2006
DOI: 10.1037/0278-7393.32.5.1019
|View full text |Cite
|
Sign up to set email alerts
|

Why people underestimate y when extrapolating in linear functions.

Abstract: E. L. DeLosh, J. R. Busemeyer, and M. A. McDaniel (1997) found that when learning a positive, linear relationship between a continuous predictor (x) and a continuous criterion (y), trainees tend to underestimate y on items that ask the trainee to extrapolate. In 3 experiments, the authors examined the phenomenon and found that the tendency to underestimate y is reliable only in the so-called lower extrapolation region--that is, new values of x that lie between zero and the edge of the training region. Existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(59 citation statements)
references
References 14 publications
6
52
0
1
Order By: Relevance
“…First, people largely anchor their responses at either zero or one. This is consistent with other observations in function learning (Kwantes & Neal, 2006), but in the present experiment, the choice of anchor was not consistent. The inconsistency of the anchor is mirrored by the second feature, which is the tendency of participants to make extreme quasi-periodic responses.…”
Section: Discussionsupporting
confidence: 82%
“…First, people largely anchor their responses at either zero or one. This is consistent with other observations in function learning (Kwantes & Neal, 2006), but in the present experiment, the choice of anchor was not consistent. The inconsistency of the anchor is mirrored by the second feature, which is the tendency of participants to make extreme quasi-periodic responses.…”
Section: Discussionsupporting
confidence: 82%
“…More generally, our demonstration shows that an established and classic theory for memory that has previously been applied to understand a suite of behaviors including (a) recognition memory (Hintzman 1984), (b) frequency judgment (Hintzman 1988), (c) cued recall (Hintzman 1986), (d) classification (Hintzman 1986), (e) function learning (Kwantes and Neal 2006), (f) judgment and decision (Dougherty et al 1999;Thomas et al 2008), (g) speech normalization (Goldinger 1998), (h) confidence/accuracy inversions in eyewitness identification (Clark 1997), (i) language processing (Rosch and Mervis 1975), (j) false memory (Arndt and Hirshman 1998), (k) memory dissociations in aging (Benjamin 2010), (l) implicit learning (Jamieson and Mewhort 2009a, 2010, (m) speeded choice (Jamieson and Mewhort 2009b), (n) associative learning (Jamieson et al 2010b, (o) the production effect in recognition memory (Jamieson et al 2016a), and (p) selective memory impairment in amnesia (Jamieson et al 2010a;Curtis and Jamieson 2018) can also be used to understand semantics. The cross-lab and cross-domain effort represents the way that science ought to progress-by developing a general account of memory and its processes in a working computational system to produce a common explanation of behavior rather than a set of labspecific and domain-specific theories for different behaviors (Newell 1973).…”
Section: Discussionmentioning
confidence: 99%
“…To date, extrapolation-based studies of function learning are comparatively sparse, but have revealed several biases in human learners. For example, people's extrapolation judgments follow linear patterns , but see Kalish et al (2004)), and more specifically tend toward functions with a positive slope and an intercept of zero (Kwantes and Neal 2006). In one instance of this bias, when people are trained using data from a quadratic function, their average predictions fall between the true function and straight lines fitted to the closest training points.…”
mentioning
confidence: 99%